Differences in the Consumption of Macro and Micro Nutrients among Stunted Toddlers in Bengkulu City - Suryani, Desri; Krisnasary, Arie; Pratiwi, Bintang Agustina; Yandrizal, Yandrizal (Jurnal Bidan Cerdas, 2024)
Introduction: Stunting remains a significant public health concern in Indonesia, with Bengkulu City reporting a prevalence of 12.9% in 2022. Consumption of macro and micronutrients is a factor directly related to toddlers' nutritional status. Objective: This study aimed to investigate the differences in macro and micronutrient consumption among stunted toddlers in Bengkulu City. Methods: A mixed-method approach with a sequential explanatory design was employed, involving 50 stunted toddlers and their mothers. Quantitative data were collected using a Food Frequency Questionnaire (FFQ), while qualitative data were obtained through interviews with six mothers. Results: The results showed no significant differences in the consumption of energy, carbohydrates, protein, fat, and zinc between toddlers with severe stunting and stunting. However, a significant difference was found in iron consumption (p=0.048), with severely stunted toddlers consuming less iron compared to stunted toddlers. Interviews revealed similar dietary patterns among mothers of both groups, with rice as the staple food and limited fish consumption.  Conclusion: The findings suggest monitoring iron-rich food consumption in stunted children is essential. Strengthening family empowerment programs, expanding educational initiatives on iron consumption, and regular nutritional monitoring are recommended to address stunting. Promotion of affordable, iron-rich foods and monitoring of iron intake by mothers and health workers are crucial in the treatment of stunting.